Changes in biological activity and toxicity of soil in sweet corn crops - E. N. Efremova; A. I. Belyaev; N. Y. Petrov (Новые технологии)
The number of soil microorganisms affect the fertility of the soil and the processes occurring in the soil microflora. An urgent research problem is the rationale for the use of intensive technologies for the cultivation of sweet corn using progressive methods for obtaining a highly productive crop based on the principles of resource conservation, biologization and ecologization. The purpose of the research is to study the toxicity and biological activity of the soil after sowing sweet corn. The tasks are to determine the biological activity and toxicity of the soil, and comparative impact of agricultural practices in the study of soil toxicity. Two-factor experiment in quadruple repetition. The experiments were carried out on the farm enterprise of Popov S.A., the Chernoyarsky district of the Astrakhan region. The research period was 2009…2015. Determination of biological activity and toxicity was carried out at the beginning of the research in 2009 and 2015. According to the assessment of the intensity of the destruction of cellulose on O.E. Pryazhnikova’s scale biological activity was characterized as strong. A close correlation dependence on experience factors was noted, the relationship between the signs was high and direct. When determining the toxicity of the soil, we came to the conclusion that at the beginning of the research favorable conditions for the development of the studied crop were formed on soils cultivated by moldboard cultivation. According to zero tillage, an increase in soil toxicity was observed, which was expressed in a decrease in seed germination, the mass of seedlings. Revisited in 2015. Soil toxicity after zero tillage decreased in all variants, seed germination increased, on average, by 5...8%. As a result of the accumulation of plant residues on the soil surface, an upper humus layer was formed, leading to a constant penetration of ai r into the soil.